Pakistan Army Green Book 2002 : Low Inensity Conflict - Pakistan Army; Editorial Board : Col. Kahn Muhammad butt; Lt. Col. Tariq Mahmood and Lt. Col. Muhammad Mushtaq (GHQ, Rawalpindi Pakistan Army, 2002)
The views expressed in this book are those of the authors and not to be taken as the official opinion or policies of the General Headquarters.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals